The Social Life of Residential Architecture: A Systematic Review on Identifying the Hidden Patterns Within the Spatial Configuration of Historic Houses - Seyedeh Maryam Moosavi; Còssima Cornadó; Reza Askarizad; Chiara Garau (Buildings, 2025)
Traditional residential architecture is more than a historical form; it is a repository of lived experiences, cultural identity, and socio-spatial organisation. However, scholarly understanding of its social life and spatial logic remains disjointed. This study aims to identify existing research gaps in the spatial configuration of historic houses by systematically reviewing the social life of residential architecture. Using the PRISMA framework, 534 peer-reviewed articles were retrieved through a rigorous screening process from the Scopus database. A combination of bibliometric analysis using VOSviewer term mapping and SankeyMATIC visualisations was employed to categorise thematic concentrations and reveal methodological and regional distributed trends. The findings identified ten dominant thematic clusters: sustainability, restoration and conservation, gender role, vernacular architecture, space syntax, semantic values, spatial characteristics, cultural studies, environmental psychology, and adaptive reuse. The strong quantitative presence in spatial metrics and qualitative dominance in cultural and gendered perspectives suggested a rich yet segmented field ripe for future mixed-method development. The findings expose pervasive research gaps in traditional residential architecture, from a lack of real-time empirical data and fragmented interdisciplinary knowledge to underutilised innovative methodologies and insufficient representation of diverse user groups, collectively highlighting the urgent need for integrated approaches to understand evolving socio-spatial dynamics.